Article Review - Virus-Like Particles: A Comprehensive Review of Design, Applications, and Future Directions - Abdzaid, Ahmed Majeed; Jabbar, Ali Sabri (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Virus-like particles (VLPs) are no longer a new approach, but rather a transformative force in vaccine development. These marvels of engineering mimic the structure of viruses, but lack the crucial genetic material for replication. This translates to a powerful one-two punch: safety and effectiveness. VLPs can be meticulously designed to target a wide range of diseases, from established threats like HPV and HBV to the ever-present challenge of cancer. Their versatility extends even further, with ongoing research exploring their potential against emerging infectious diseases like COVID-19. However, the road to VLP-based vaccines isn't without its hurdles. Manufacturing these particles can be intricate and expensive, and ensuring their stability during storage remains a challenge. Additionally, some viruses mutate rapidly, rendering vaccines targeting specific strains less effective. Undeterred, researchers are actively tackling these obstacles. Advancements in genetic engineering, nanotechnology, and adjuvants (compounds that enhance immune response) hold great promise for making VLP vaccines even more potent and adaptable. The future may even see VLPs joining forces with other vaccine platforms, like mRNA vaccines, creating a new generation of powerful and versatile tools for disease prevention. The present review article aimed to highlight different aspects of VLPs including their design, advantages, challenges, and future.